2013
DOI: 10.1007/s11745-013-3855-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Structural Elucidation of Triacylglycerols in Krill Oil by Chromatographic Techniques

Abstract: The content of triacylglycerols (TAG) in krill oil is generally omitted from the labels of commercial supplements and unacknowledged in studies aimed at proving its health benefits. The present study demonstrates that TAG compounds, in addition to phospholipids and lysophospholipids, are an important lipid class in pure krill oil. The fatty acid composition of TAG molecules from krill oil and their distribution on the backbone of TAG structures were determined by gas chromatography and liquid chromatography ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 17 publications
5
41
2
Order By: Relevance
“…Nevertheless, stearic acid (18:0) was at similar values in the three fractions. These results are in agreement with the results showed by Araujo et al (2014) in which the 14:0 represented 17.5 % in TAG fraction and only 4.2 % in PL while 16:0 was contained in 25.0 % in this latter fraction against 18.9 % in TAG. The MUFA content decreased as the polarity of the fraction increased, and hence, F1, F2, and F3 had contents of 35, 28, and 17 %, respectively.…”
Section: Fame Analysis By Gc-ms Of Krill Oil and Fractionssupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, stearic acid (18:0) was at similar values in the three fractions. These results are in agreement with the results showed by Araujo et al (2014) in which the 14:0 represented 17.5 % in TAG fraction and only 4.2 % in PL while 16:0 was contained in 25.0 % in this latter fraction against 18.9 % in TAG. The MUFA content decreased as the polarity of the fraction increased, and hence, F1, F2, and F3 had contents of 35, 28, and 17 %, respectively.…”
Section: Fame Analysis By Gc-ms Of Krill Oil and Fractionssupporting
confidence: 93%
“…Likewise, the value of 0.14 obtained for the omega-6/omega-3 ratio in this study was in the same range as those reported previously in other studies by Ju et al (2009) and Kassis et al (2012). The same happened for the EPA/DHA ratio of 2.9:1, which was in agreement with the value reported for the KO manufacturer of 2.5:1 and Ju et al (2009) with 2.8:1 and somewhat higher than the value reported by Kolakowska et al (1994) and Araujo et al (2014) of 2:1 in comparable samples.…”
Section: Fame Analysis By Gc-ms Of Krill Oil and Fractionssupporting
confidence: 93%
See 1 more Smart Citation
“…Krill contain LC n-3 PUFA mainly as phospholipids (38) but also as TAG (31) . E. superba contains the highest concentration of EPA and DHA compared to other krill species (39) .…”
Section: Krillmentioning
confidence: 99%
“…For example, krill oil usually contains different lipid classes, including phospholipids, triacylglycerols, free fatty acids and cholesterol (Araujo et al, 2014) to the extent that an effective extraction protocol is required prior to the analysis of phospholipids by LCMS n to prevent interference from other lipid classes, ensure data quality and improve the accuracy of the identification and quantification steps.…”
Section: Introductionmentioning
confidence: 99%